Squamous cell carcinoma of the oral tongue: an analysis of prognostic factors - G. El-Husseiny, A. Kandil, A. Jamshed, Y. Khafaga, M. Saleem,* A. Allam, N. Al-Rajhi, A. Al-Amro, A. (Blackwell Synergy, 2000)
Carcinoma of the tongue is one of the common tumours of head and neck, and carcinoma of the oral cavity accounts for 5.6% of patients with cancer in Saudi Arabia.1 This relatively high incidence has been attributed to chewing tobacco (Shamma), which is commonly used in the south of the country.